2018
DOI: 10.1161/jaha.117.007124
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Myocardial Fibrosis: Revealing the Natural History of Fibrogenesis in Fabry Disease Cardiomyopathy

Abstract: BackgroundCardiomyopathy is a major determinant of overall Fabry disease (FD) prognosis, with the worst outcomes in patients with myocardial fibrosis. Late gadolinium enhancement is currently the gold standard for evaluation of replacement myocardial fibrosis; however, this event is irreversible, thus identification of biomarkers of earlier diffuse fibrosis is paramount.Methods and ResultsType I collagen synthesis and degradation biomarkers (PICP [carboxyterminal propeptide of procollagen type I], ICTP [carbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…On the other hand, in a study in which 66% of patients had cardiac fibrosis at the onset of the disease, baseline serum levels of PIIINP, procollagen type I carboxy-terminal propeptide (PIPP) and collagen type I carboxy-terminal telopeptide (CICT) were increased [127]. Finally, in a study that Aguiar et al [128] conducted in a cohort of patients grouped by the severity of cardiomyopathy, serum levels of biomarkers involved in synthesis (PIPP) and degradation (CICT, MMP1, MMP2) of collagen type I adjusted for bone turnover were analyzed and found that adjusted PIPP levels were significantly increased in patients, including the asymptomatic, being higher in those with ventricular hypertrophy. Such increased levels in asymptomatic patients suggested that adjusted PIPP could be used as an early biomarker of cardiac dysfunction.…”
Section: New Biomarkers Related To Cardiomyopathymentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, in a study in which 66% of patients had cardiac fibrosis at the onset of the disease, baseline serum levels of PIIINP, procollagen type I carboxy-terminal propeptide (PIPP) and collagen type I carboxy-terminal telopeptide (CICT) were increased [127]. Finally, in a study that Aguiar et al [128] conducted in a cohort of patients grouped by the severity of cardiomyopathy, serum levels of biomarkers involved in synthesis (PIPP) and degradation (CICT, MMP1, MMP2) of collagen type I adjusted for bone turnover were analyzed and found that adjusted PIPP levels were significantly increased in patients, including the asymptomatic, being higher in those with ventricular hypertrophy. Such increased levels in asymptomatic patients suggested that adjusted PIPP could be used as an early biomarker of cardiac dysfunction.…”
Section: New Biomarkers Related To Cardiomyopathymentioning
confidence: 97%
“…Such increased levels in asymptomatic patients suggested that adjusted PIPP could be used as an early biomarker of cardiac dysfunction. Some of the markers mentioned above have been associated with cardiac manifestations, such as endocardial fractional shortening, ventricular hypertrophy, ventricular dysfunction, maximal left-atrial size or degree of cardiac fibrosis [63,78,125,128], suggesting that mediators of inflammation, or ECM remodeling or regulation may contribute to the detection of cardiac injury, and be useful as indicators of left ventricular dysfunction.…”
Section: New Biomarkers Related To Cardiomyopathymentioning
confidence: 99%
“…In this study, there was no correlation between NT-proBNP and our proteomics assay (with the exception of RSU1, r s = 0.21; P = 0.028) suggesting that the majority of our candidate peptides may be tracking myocyte hypertrophy (LV mass and MWT) and fibrosis (native T1 and LGE) rather than myocardial stress. Though results from enzyme-linked immunosorbent assays appraising collagen synthesis biomarkers in venous blood samples of HCM patients have previously been conflicting (40,64), recent data in Fabry disease (a genetic lysosomal storage disorder resulting in pathological cardiac hypertrophy) demonstrated a correlation between levels of type I collagen synthesis and degradation biomarkers in blood, and LV mass and scar by CMR (65). This would fit with our findings where a different set of proteomics plasma markers of fibrosis, similarly correlate with LV wall thickness, mass and scar by CMR in LVH+ HCM.…”
Section: Clinical Correlationsmentioning
confidence: 99%
“…As we previously reported, the p.F113L GLA gene mutation is associated with a high burden of cardiac and CNS manifestations [25,26]. Hearing loss was a common manifestation and age-matched hearing thresholds by frequency are worse in FD than in the general population [18,25,26]. One possible explanation is that the vascular peripheral lesioning could correlate with higher CNS microvascular burden (hearing loss was correlated with microalbuminuria).…”
Section: Discussionmentioning
confidence: 72%